Spatial Planning Based on Geoecology Study For Settlement Area Zonation Direction in Coastal Area of Kulon Progo District Daerah Istimewa Yogyakarta Province - Juliansyah Harahap (Elkawnie: Journal of Islamic Science and Technology, 2015)
This research was conducted at Kulon Progo coastal area of Daerah Istimewa Yogyakarta Province. The objectives were to define geoecosystem units spread by examining constituent parameters of coastal geoecology system, to evaluate suitability of existing settlement zone regarding the characteristic of geoecology type, to inventory environment issues and to set the direction of settlement zone development which accommodates the characteristic of geoecology type. This research used geoecology approach based on geomorphology process and landform as a basic setting of geoecosystem unit as an analytical unit. The Method used was a survey using stratified random sampling technique. Data analysis was arranged descriptively and by spatial modeling using Arc Gis version 9.3 software. This research produced the identification of geoecosystem units in this area.The identified largest area were dominated by coastal alluvial plain geoecosytem unit and sand dunes geoecosystem unit ,by 2.685,461 Ha (43,05%) and 1.986,121Ha (31,84%), respectively. Old beach ridge geoecosistem unit and coastal alluvial plain were the most suitable, based on geoecology characteristic, as a direction of settlement area zonation development. This recommendation of comprehensive settlement zonation was set to solve whole environment issues and integrated by involving whole stakeholders. Keywords :